CyberAffair: Fenomena Perselingkuhan Di Era Digital Perspektif Kaidah Fiqh - Zakirman, Al Fakhri; Manda, Rifky Mei; Rohana, Siti; Mariska, Revi (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
The phenomenon of cyberaffair or digital infidelity is one of the negative consequences of technological advancements in the digital era, where emotional and romantic relationships can form through social media, messaging apps, or other online platforms. This article examines the phenomenon from the perspective of Islamic legal principles (fiqh) using a descriptive qualitative method aimed at providing guidance on addressing this issue based on Islamic law. Several relevant principles include al-ashlu fil asyaa’i al-ibahah (the default ruling on things is permissibility), idzajtama’a al-haram wa al-halal ghalaba al-haram (when the lawful and unlawful combine, the unlawful prevails), dar'ul mafasid muqaddam ‘ala jalbil mashalih (preventing harm is prioritized over obtaining benefits), and adh-dharar yuzal (harm must be removed). Through these principles, the article emphasizes the importance of preventing digital infidelity due to its detrimental effects on morality, marital relationships, and social life. In conclusion, Islam provides clear guidance on maintaining boundaries in digital interactions to avoid greater harm in personal and family life.